Best Practice Recommendations for Pediatric Otolaryngology during the COVID-19 Pandemic. (June 2020) - Bann, Darrin V.; Patel, Vijay A.; Saadi, Robert; Goyal, Neerav; Gniady, John P.; McGinn, Johnathan D.; Goldenberg, David; Isildak, Huseyin; May, Jason; Wilson, Meghan N.
Objective: To review the impact of coronavirus disease 2019 (COVID-19) on pediatric otolaryngology and provide recommendations for the management of children during the COVID-19 pandemic. Data Sources: Clinical data were derived from peer-reviewed primary literature and published guidelines from national or international medical organizations. Preprint manuscripts and popular media articles provided background information and illustrative examples. Methods: Included manuscripts were identified via searches using PubMed, MEDLINE, and Google Scholar, while organizational guidelines and popular media articles were identified using Google search queries. Practice guidelines were developed via consensus among all authors based on peer-reviewed manuscripts and national or international health care association guidelines. Strict objective criteria for inclusion were not used due to the rapidly changing environment surrounding the COVID-19 pandemic and a paucity of rigorous empirical evidence. Conclusions: In the face of the COVID-19 pandemic, medical care must be judiciously allocated to treat the most severe conditions while minimizing the risk of long-term sequelae and ensuring patient, physician, and health care worker safety. Implications for Practice: The COVID-19 pandemic will have a profound short- and long-term impact on health care worldwide. Although the full repercussions of this disease have yet to be realized, the outlined recommendations will guide otolaryngologists in the treatment of pediatric patients in the face of an unprecedented global health crisis.